2017
DOI: 10.1021/acschemneuro.7b00017
|View full text |Cite
|
Sign up to set email alerts
|

An ortho-Iminoquinone Compound Reacts with Lysine Inhibiting Aggregation while Remodeling Mature Amyloid Fibrils

Abstract: Protein aggregation is a hallmark of several neurodegenerative diseases, including Alzheimer's and Parkinson's diseases. It has been shown that lysine residues play a key role in the formation of these aggregates. Thus, the ability to disrupt aggregate formation by covalently modifying lysine residues could lead to the discovery of therapeutically relevant antiamyloidogenesis compounds. Herein, we demonstrate that an ortho-iminoquinone (IQ) can be utilized to inhibit amyloid aggregation. Using alpha-synuclein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…We opted to load the MPs with a small molecule called ortho-IQ that we previously characterized as an antiamyloidogenic compound. 28 The loading process was performed by incubating IQ with MP. Then, the sample was sonicated for 30 min to permeabilize the surface of the MPs, and in the end of 24 h incubation, the loaded MPs were centrifuged and washed to remove free IQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We opted to load the MPs with a small molecule called ortho-IQ that we previously characterized as an antiamyloidogenic compound. 28 The loading process was performed by incubating IQ with MP. Then, the sample was sonicated for 30 min to permeabilize the surface of the MPs, and in the end of 24 h incubation, the loaded MPs were centrifuged and washed to remove free IQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, our recent work has shown that IQ is an excellent option to inhibit amyloid α-syn aggregation and the remodeling of mature fibrils into amorphous species. 28 Herein, we produced EGCG MPs through an oxidative protocol described previously. 22 After a few modifications, we produced EGCG MPs that were characterized by several biophysical techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These functional microparticles, with oxidized EGCG as carrier, have been shown to inhibit α-syn aggregation, reduce the cytotoxicity of oligomers and, modestly, remodel mature fibrils ( Fernandes et al, 2020 ). Moreover, when the EGCG microparticle was loaded with an additional amyloidogenesis inhibitor, ortho-iminoquinone ( Largeron and Fleury, 2012 ; Fernandes et al, 2017 ), its activity increased, demonstrating a synergistic action between the microcarrier and the loaded molecule ( Fernandes et al, 2020 ).…”
Section: Drug Delivery Systems Containin Epigallocatechin-gallatementioning
confidence: 99%
“…Analyzing α-syn species by biochemical approaches, another small molecule, an ortho-iminoquinone (IQ) was shown to reduce amyloid aggregation by reacting with lysine residues. IQ also reacted with free amines within the amyloid fibrils preventing their dissociation and seeding capacity [232].…”
Section: Molecules Directly Interacting With α-Synmentioning
confidence: 99%